Atomoxetine for amphetamine-type stimulant dependence during buprenorphine treatment: A randomized controlled trial. (1st May 2018) - Schottenfeld, Richard S.; Chawarski, Marek C.; Sofuoglu, Mehmet; Chooi, Weng-Tink; Zaharim, Norzarina M.; M. Yasin, M. Azhar; Ahmad, Imran; Syed Jaapar, Sharifah Zubaidiah; Vicknasingam, B. Kasinather
Highlights: This pilot study evaluated atomoxetine for treating amphetamine type stimulant (ATS) use disorder. Atomoxetine 80 mg was well tolerated, safe, and effective for reducing ATS use. Atomoxetine was also associated with greater improvements in depressive symptoms. Abstract: Background: Amphetamine type stimulants (ATS) use is highly prevalent and frequently co-occurs with opioid dependence in Malaysia and Asian countries. No medications have established efficacy for treating ATS use disorder. This study evaluated the safety, tolerability, and potential efficacy of atomoxetine for treating ATS use disorder. Methods: Participants with opioid and ATS dependence (N = 69) were enrolled in a pilot, double-blind, placebo-controlled randomized clinical trial; all received buprenorphine/naloxone and behavioral counseling and were randomized to atomoxetine 80 mg daily (n = 33) or placebo (n = 33). The effect size of the between-group difference on the primary outcome, proportion of ATS-negative urine tests, was estimated using Cohen's d for the intention-to-treat (ITT) sample and for higher adherence subsample (≥60 days of atomoxetine or placebo ingestion). Results: Participants were all male with mean (SD) age 39.4 (6.8) years. The proportion of ATS-negative urine tests was higher in atomoxetine- compared to placebo-treated participants: 0.77 (0.63–0.91) vs. 0.67 (0.53–0.81, d = 0.26) in the ITT sample and 0.90 (0.75–1.00) vs. 0.64 (0.51–0.78, d = 0.56) in the higher adherence subsample. The proportion of days abstinent from ATS increased from baseline in both groups (p < 0.001) and did not differ significantly between atomoxetine- and placebo-treated participants (p = 0.42). Depressive symptoms were reduced from baseline in both groups (p < 0.02) with a greater reduction for atomoxetine- than placebo-treated participants (p < 0.02). There were no serious adverse events or adverse events leading to medication discontinuation. Conclusions: The findings support clinical tolerability and safety and suggest potential efficacy of atomoxetine for treating ATS use disorder in this population.